PERSEPSI DAN PENGALAMAN PENDERITA DALAM PENGOBATAN KUSTA DI KABUPATEN NGAWI - WIJAYANTI , ANISA CATUR (2011)
This research were to know about perceptions and experiences of patients of leprosy treatment in Ngawi Regency. Data collection was taken by dept interview. The collected data was analysed by content analysis and descriptive statistic. This research subjects were the new leprosy patients who ought to still do the leprosy treatment in Ngawi Regency. Research population were 55 people. As many as 30 become samples. The results showed 16 respondents (53.33%) knew a correct understanding of leprosy, 23 respondents (76.67%) did not knew the exact cause of leprosy, 25 respondents (83.33%) know the signs or symptoms of leprosy correctly, 15 respondents (50%) know the way of transmission of leprosy correctly, there were 2 respondents (6.67%) who stopped treatment at the clinic because they did not see any changes in the illness. Perception and experiences of respondents of leprosy treatment indicated most respondents believe to be recovered by leprosy treatment at Puskesmas and respondents did not try to hide their leprosy from the society. Puskesmas officers had important role to increase patient knowledge and kept the patient finishing their medications.